On Non-negative Solutions to Space-Time Partial Differential Equations of Higher Order - Kristian Evans (Springer Proceedings in Mathematics and Statistics, 2022)
We discuss when certain higher order partial differential operators in space and time admit non-negative solutions which have a semigroup representation as well as a representation by some associated Markov process.